Analysis of the nutritional status of pregnant women in times of Covid-19 attached to the type ́ ́a ́ ́ health center Toacaso – Ecuador (Horizontes de Enfermería, 2022)
The adequate nutritional status in the pregnant woman preserves the healthy physiological state and an adequate immune response to possible infection by (COVID-19). The objective of the research process was to analyze the nutritional status of pregnant women in times of COVID-19, determining (BMI) preconception, weight gain, prevalence of comorbidities and obstetric risk in prenatal control. In a first-level health care unit in the province of Cotopaxi, Ecuador, during the first half of 2021. The study had a quantitative, non-experimental, descriptive and cross-sectional field approach. The population was consisted of 45 pregnant women. Data were collected through a nutritional assessment sheet validated by Essalud.  The most relevant data reflect that 71.11%, have a primary education level, in the variable comorbidities it is known that 2.22% suffer from arterial hypertension, 22.22% was diagnosed with overweight, 8.89% with obesity. 26.67% corresponds to pregnant adolescents of extreme fertile age under 19 years of and 8.89% pregnant women over 35 years of age. 20.00% of women who started with an overweight preconception BMI, 8.89% started with an obesity preconception BMI. In correlation with these data, 26.67% of pregnant women obtained insufficient weight gain, 62.22% obtained adequate weight gain, while 11.11% gained excess weight. It is of great relevance to mention that 86.67% of pregnant women are categorized as high risk and 6.67% are categorized with a very high risk.
Keywords: Nutritional status; pregnant women; Covid – 19; body mass index